A longitudinal investigation of landing biomechanics following anterior cruciate ligament reconstruction. (July 2021) - Webster, Kate E.; Ristanis, Stavros; Feller, Julian A.
Abstract: Objective: Abnormal movement patterns have been shown during landing in patients who have undergone anterior cruciate ligament (ACL) reconstruction surgery. The purpose of this study was to investigate landing biomechanics over time in this patient group to determine whether asymmetry between limbs reduced with time and after a return to physical activity. Design: Prospective longitudinal study. Setting: Biomechanics laboratory. Participants: Fourteen patients who had undergone ACL reconstruction surgery. Main outcome measure: Single limb landing assessments were made at two time points; within the first year (mean of 10 months) and at 3 years (after patients had returned to sport) following ACL reconstruction. Three-dimensional motion analysis was used to record kinematic and kinetic variables, which were compared across time and limb using ANOVA models. Results: Most biomechanical variables showed little change over time except for the external knee adduction moment at the operated knee, which increased (effect size d = 0.5), but remained less than the contralateral side. In the sagittal plane, asymmetrical landing patterns were seen at both assessments. Patients landed with reduced knee flexion angles (effect size range 0.76–0.9) and moments (effect size range 0.56–0.9) compared to the uninjured limb and made compensations for this by increasing the hip flexion moment (effect size range d = 0.6–0.75). Conclusions: Asymmetrical landing biomechanics persisted at three years after ACL reconstruction in athletes who returned to sporting activity. Long term implications of controlling the landing by increasing the hip moment are unknown and require further investigation. Highlights: The knee adduction moment was the only biomechanical variable to change over time in the ACL reconstructed limb. Asymmetrical landing patterns persisted in athletes who had returned to sport 3 years after ACL reconstruction. Increased hip moments suggest a stabilization strategy that transfers control from the knee to hip after ACL reconstruction.